2019
DOI: 10.1371/journal.pone.0225221
|View full text |Cite
|
Sign up to set email alerts
|

Stroke risks in women with dysmenorrhea by age and stroke subtype

Abstract: BackgroundDysmenorrhea and stroke are health problems affecting women worldwide in their day-to-day lives; however, there is limited knowledge of the stroke risk in women with dysmenorrhea, and there have been no studies assessing the specific distribution of stroke subtypes. This case-control study assessed stroke subtypes by age and the role of comorbidities in women with dysmenorrhea.Methods and findingsData obtained between 1997 and 2013 from Taiwan’s health insurance database identified 514 stroke cases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
(25 reference statements)
1
13
0
Order By: Relevance
“… 7 Attempts have been made in previous studies to understand if dysmenorrhea predisposes women to vascular complications such as high blood pressure, hypertension, and stroke, but whether the severity of dysmenorrhea correlates to the susceptibility to these vascular complications remained unexplained. 8 9 10 Based on this, we conducted this study using female university students to first establish the reliability of a pain biomarker, contactin 1, for the assessment of the severity of dysmenorrhea, by correlating with the NRS-11 pain scale of each participant, and also correlated with the biomarkers of vascular health; the vascular cell adhesion molecule 1 and angiotensin II.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Attempts have been made in previous studies to understand if dysmenorrhea predisposes women to vascular complications such as high blood pressure, hypertension, and stroke, but whether the severity of dysmenorrhea correlates to the susceptibility to these vascular complications remained unexplained. 8 9 10 Based on this, we conducted this study using female university students to first establish the reliability of a pain biomarker, contactin 1, for the assessment of the severity of dysmenorrhea, by correlating with the NRS-11 pain scale of each participant, and also correlated with the biomarkers of vascular health; the vascular cell adhesion molecule 1 and angiotensin II.…”
Section: Introductionmentioning
confidence: 99%
“…Although stroke and dysmenorrhea are related to mutual risk factors, few researchers have investigated the association between the two conditions. A recent case-control study using insurance-claim data of women with dysmenorrhea in Taiwan suggested that stroke-related disorders are more prevalent in stroke cases than in nonstroke controls (21) Stroke can result in physical disability and dependence on others, both of which impose high economic costs (2). Stroke costs an estimated $34 billion each year in the United States (22).…”
Section: Introductionmentioning
confidence: 99%
“…It should, however, be noted that it remains unclear how the occurrence of stroke among women with dysmenorrhea affects the cost of care. Few studies have evaluated whether the stroke types and costs in women with dysmenorrhea differ from those in women without dysmenorrhea (21). The occurrence of dysmenorrhea and stroke varies by age (3).…”
Section: Introductionmentioning
confidence: 99%
“…Although stroke and dysmenorrhea are related to mutual risk factors, few researchers have investigated the association between the two conditions. A recent case-control study using insurance-claims data of women with dysmenorrhea in Taiwan suggested that stroke-related disorders are more prevalent in stroke cases than in non-stroke controls [20]. The disorders included hypertension (adjusted odds ratio [ Stroke can result in physical disability and dependence on others, both of which impose high economic costs [2].…”
Section: Introductionmentioning
confidence: 99%
“…It should, however, be noted that it remains unclear how the occurrence of stroke among women with dysmenorrhea affects the cost of care. Limited study has evaluated whether the stroke types and costs in women with dysmenorrhea differ from those in women without dysmenorrhea [20]. The occurrence of dysmenorrhea and stroke vary by age [3].…”
Section: Introductionmentioning
confidence: 99%